Skin‐derived precursor schwann cell myelination capacity in focal tibial demyelination. Issue 2 (15th May 2014) - Grochmal, Joey; Dhaliwal, Sundeep; Stys, Peter K.; van Minnen, Jan; Midha, Rajiv
ABSTRACT Introduction: Skin‐derived precursor cells (SKPs) are neural crest progenitor cells that can attain a Schwann cell–like phenotype through in vitro techniques (SKP‐SCs). We hypothesized that SKP‐SCs could produce mature myelin and, in doing so, facilitate the recovery of a focal demyelination injury. Methods: We unilaterally injected DiI‐labeled, green fluorescent protein (GFP)‐producing SKP‐SCs into the tibial nerves of 10 adult Lewis rats (with contralateral media control), 9 days after bilateral doxorubicin injury (0.38 μg). Tibial compound motor action potentials (CMAPs) were followed for 57 days. A separate morphometric cohort also included a Schwann cell injection group. Results: SKP‐injected nerves recovered fastest in terms of electrophysiology and morphometry. SKP‐SCs formed morphologically mature myelin, accounting for 15.3 ± 5.3% of the total myelin in SKP‐SC–injected nerves. Conclusions: SKP‐SCs are robustly capable of myelination. They improve the recovery of a focal tibial nerve demyelination model by myelinating a measured percentage of axons. Muscle Nerve 50:262–272, 2014